Structural control and magnetic properties of three Co(II) coordination polymers based on 6-(3, 5-dicarboxylphenyl)nicotinic acid. (8th May 2017) - Hu, Tuoping; Wang, Xiaoxiao; Xue, Zhijia; Zhang, Xiao; Wang, Xiaoqing
Graphical abstract: The coordination preferences of different N-donor co-ligands in synthetic procedures of three complexes based on 6-(3, 5-dicarboxylphenyl)nicotinic acid and transition metal ions Co(II). Abstract: Three coordination polymers (CPs) based on 6-(3, 5-dicarboxylphenyl)nicotinic acid (H3 DCPN) and N-donor linkers, {[Co(HDCPN)(bbib)(H2 O)]·2H2 O} n (1 ), [Co(HDCPN)(bbib)] n (2 ), and {[Co(HDCPN)(bpy)0.5 (H2 O)]·H2 O} n (3 ) (bbib = 1, 4-bis(benzimidazo-1-ly)benzene, bpy = 4, 4′-bipyridine), were synthesized under solvothermal conditions. Single-crystal X-ray diffraction analysis reveals that complexes1 –3 are 3D supramolecular structures. Complexes1 and2 display 2D 4-connected sql networks, and complex3 shows a 2D (3, 4)-c network, which are all further packed into 3D supramolecular structures by hydrogen bonds. It is noteworthy that the adjacent layers interpenetrate with each other to generate 2D + 2D → 2D network in complex1, and complex3 possesses an intriguing 2D + 2D → 3D parallel polycatenation architecture. The different structures for complexes1 and2 can be attributed to temperature-dependent structural variation. Furthermore, the magnetic properties of complexes2 and3 have been also investigated, and both of them exhibit weak antiferromagnetic coupling interactions.